A peek behind the mask Filipino lesbians closeting, social networking, views on HIV and sexual behavior and social support. - Cordova, Marie J Thessany
A study of nine (9) lesbians was done to understand their closeting experiences, social support, social networking behavior, and views on HIV and sexual behavior. The participants were from different provinces in the Visayas. The participants were selected through snowball sampling. The results shows that they have similar experiences in closeting, but they differ in some aspects, such as their ages when they experienced confusion and the first people they opened up to. They seek social support from their friends. Most of the participants claimed that they are at low risk of acquiring HIV. They also have sufficient knowledge about it, which in turn, has affected their sexual behavior.